The Role of Islamic Journalists in Fighting Hate Speech - M. Yoserizal Saragih (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This paper reviews the role of journalism in preventing hate speech or hate speech that is currently rife in various media. The purpose of this paper is to increase knowledge about what is happening at this time. This paper is a descriptive analysis which aims to describe, take an inventory, and analyze the conditions being investigated in a systematic, factual and accurate manner, and then a conclusion can be drawn from the results of the study. The results of the discussion show that Islamic journalism is known as a journalist based on values and norms that adopt principles from the Qur'an and Hadith. Islamic journalism is also known as the enforcer of amar ma'ruf nahi munkar. In preventing hate speech or hate speech, there are several steps to counteract it,carry out awareness activities in the community to be wiser and smarter in using the media, cultivate tabayun attitudes, establish cooperation, and provide sanctions/fines. In addition to these steps, the role of Islamic journalism in warding off hate speech is in the form of providing education, broad knowledge, and providing direction in media wisely, wisely.ethics, manners, and full of courtesy, in using the media by adopting or applying the principles of sidhhiq, amanah, tabligh and fhatonah based on the example of the Prophet Muhammad.